Mechanics-- Microstructure-- Corrosion coupling : concepts, experiments, modeling and cases - Blanc, Christine; Aubert, Isabelle (ISTE Press, 2019)
Mechanics - Microstructure - Corrosion Coupling: Concepts, Experiments, Modeling and Cases presents the state-of-the-art on scientific and technological developments relating to the durability of materials and structures subjected to mechanical and environmental stress in industries such as energy, aeronautics, chemistry and oil. Experimental, theoretical and numerical aspects are tackled at different scales, providing readers with the most advanced tools and scientific approaches to apprehend coupling phenomena by understanding associated mechanisms, identifying variables of the first order, and proposing strategies to control and/or extend the lifespan of structures in a multi-process coupling situation. In addition, the book presents the latest advances in research in these areas (hydrogen embrittlement, stress corrosion, fatigue, etc.), especially in the consideration of the multi-scale aspect of the phenomena in the implementation of dedicated experiments.